Consumer Behavior dan Kenyamanan Belanja Terhadap Keputusan Memilih Belanja pada Toko Ritel Modern di Bojonegoro - Kustaji, K; Agustino, M. Rizqi; Noor, Fauzian; Budianto, B; Calista, Sativa Fairuz (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the influence of consumer behavior and consumer shopping convenience in determining shopping decisions at modern retail stores. This type of research uses data collection methods through observation, documentation and questionnaires. Using 100 respondents as a sample. The method for examining information in this research is direct examination with the Statistical Product and Service Solution (SPSS) 25 application software. The variables used are Consumer Behavior (X1), Consumer Convenience (X2) and Choice Decisions (Y). The findings of this research show that consumer behavior and consumer comfort have a significant influence on shopping decisions. The results show that consumer behavior influences voting decisions. Likewise, consumer comfort variables influence the decision to choose a modern retail store.